Maternal and child health after injuries: a two-year follow-up of a nationally representative sample. (March 2019) - Alghnam, S.; Bell, T.M.; Cook, L.J.; Alqahtani, F.; Castillo, R.
Abstract: Objective: The objective of this study was to examine the association between childhood injury and health outcomes among survivors and their mothers using a national survey in the United States (US). Study design: This was a longitudinal analysis of a nationally representative sample. Methods: Secondary analysis of the 1997–2013 Medical Expenditure Panel Survey (MEPS) was performed. Children (aged 2–18 years) with or without injuries were followed up for two years. Injuries captured in the study were those associated with at least one hospitalization, emergency department visit, or office-based visit. Outcome measures were child and maternal general and mental health status. Multiple mixed-logistic regressions were used with suboptimal health defined as the response of poor or fair health versus good, very good, or excellent health. Results: Of the 63, 422 children analyzed, 3251 (4.9%) were injured, representing 3.6 million US children. Injured children were more likely to be male, white, and older than those without injuries ( P  < 0.01). About a fifth of injured children suffered head injuries. Injuries were strongly associated with suboptimal general and mental health status in children (adjusted odds ratios [AORs], 1.35 and 1.36, respectively, P  < 0.05). Mothers of children with injuries were also more likely to report suboptimal mental health (AOR, 1.30, P  < 0.05). Conclusion: Injuries among children are associated with lasting adverse effects in general and mental health. To improve health outcomes of pediatric injuries, further follow-up care may be needed to ensure that they return to pre-injury health levels. These results highlight the importance of primary prevention and the long-term impact of injuries on the health of children and their mothers. Highlights: Little is known on the long-term effects of injuries on the health of children and their mothers. About a fifth of US injured children suffered head injuries. Injuries were significantly associated with lower health status among children and first year.